Quality Improvement in Neonatal Intensive Care Units - Eun Sun Kim (Korean Society of Neonatology, 2018)
Even with the increasing number of high risk infants, neonatal care in Korea has undergone development with improved survival rate. This rapid improvement in the outcomes brought care quality in neonatal intensive care unit (NICU) to the surface. Quality improvement (QI) involves safe, timely, effective, efficient, equitable, and patient-centered care. In this review, methods of QI are described with examples of NICU QI topics. Each NICU can voluntarily develop a QI project, but systematic supports are essential. As human and systemic resources in NICUs in Korea are insufficient, institutional and national supports are necessary to attain QI. Furthermore, collaborative neonatal network can provide a QI standard and evidence based-medicine, as well as QI research.